Rapid screening and identification of bioactive compounds specifically binding to beta 2-adrenoceptor from San-ao decoction using affinity magnetic fine particles coupled with high-performance liquid chromatography-mass spectrometry - Fuhuan Fei; Huanmei Sun; Xixi Cheng; Jiajun Liu; Jing Wang; Qian Li; Yajun Zhang (BMC, 2018)
Abstract Background San-ao decoction (SAD) has been widely used in Chinese medicine against respiratory diseases, such as asthma and rhinallergosis. The bioactive compounds for such pharmacological action remain unknown. Methods We developed a methodology to isolate the bioactive compounds of SAD. The assay involved the immobilization of beta 2-adrenoceptor (β 2-AR) onto magnetic fine particles, the capture of target compounds by the immobilized receptor, the identification of the receptor bound compounds by reversed-phase high-performance liquid chromatography coupled with tandem mass spectrometry. Results Vicenin, shaftoside, isoshaftoside, liquiritin apioside and isoliquiritin apioside were identified as β 2-AR ligands in SAD extract. The binding of these compounds to β 2-AR occurred on serine169, serine170 and phenylalanine256 of the receptor. Conclusions The developed methodology has high stability and specificity for recognizing and isolating target compounds. It is an alternative method for rapidly screening bioactive compounds of immobilized receptor from Chinese prescriptions.